RETRACTED ARTICLE: Assessment of fetal intraventricular diastolic fluid dynamics using ultrasound vector flow mapping - Shu, Qinglan; Wang, Yi; Lin, Xinyi; Xie, Shenghua; Wang, Zhengyang; Wang, Sijia; Yin, Lixue (BMC cardiovascular disorders, 2023)
Abstract Objective The purpose of this study was to investigate the feasibility of visualizing and quantifying the normal pattern of vortex formation in the left ventricle (LV) and right ventricle (RV) of the fetal heart during diastole using vector flow mapping (VFM). Methods A total of 36 healthy fetuses in the second trimester (mean gestational age: 23 weeks, 2 days; range: 22–24 weeks) were enrolled in the study. Color Doppler signals were recorded in the four-chamber view to observe the phase of the diastolic vortices in the LV and RV. The vortex area and circulation were measured, and parameters such as intraventricular pressure difference (IVPD), intraventricular pressure gradient (IVPG), and average energy loss (EL_AVG) were evaluated at different diastolic phases, including isovolumic relaxation (D1), early diastole (D2), and late diastole (D3). Results Healthy second-trimester fetal vortex formations were observed in both the LV and RV at the end of diastole, with the vortices rotating in a clockwise direction towards the outflow tract. There were no significant differences in vortex area and circulation between the two ventricles (p > 0.05). However, significant differences were found in IVPD, IVPG, and EL_AVG among the diastolic phases (D1, D2, and D3) (p < 0.05). Trends in IVPD, IVPG, and EL_AVG during diastole (D1-D2-D3) revealed increasing IVPD and EL_AVG values, as well as decreasing IVPG values. Furthermore, during D3, the RV exhibited significantly higher IVPD, IVPG, and EL_AVG compared to the LV (p > 0.05). Conclusion VFM is a valuable technique for analyzing the formation of vortices in the left and right ventricles during fetal diastole. The application of VFM technology has the potential to enhance the assessment of fetal cardiac parameters.